The Origins of Cognitive Skills and Non-cognitive Skills: The Long-Term Effect of in-Utero Rainfall Shocks in India - Grace Chang; Marta Favara; Rafael Novella (Institute of Labor Economics (IZA), 2020)
Skills are an important predictor of labour, education, and wellbeing outcomes. Understanding the origins of skills formation is important for reducing future inequalities. This paper analyses the effect of shocks in-utero on human capital outcomes in childhood and adolescence in India. Combining historical rainfall data and longitudinal data from Young Lives, we estimate the effect of rainfall shocks in-utero on cognitive and non-cognitive skills development over the first 15 years of life. We find negative effects of rainfall shocks on receptive vocabulary at age 5, and on mathematics and non-cognitive skills at age 15. Also, shocks occurred after the first trimester are more detrimental for skills development. Our findings support the implementation of policies aiming at reducing inequalities at very early stages in life.
Keywords: J24; I14; 330; skills formation; in-utero; rainfall shocks; India